Recurrent Esophageal Stricture as a Result of Esophageal Diverticulum: Case Report - Renaldi, Kaka; Prabowo, Muhamad Reza (The Indonesian Society for Digestive Endoscopy, 2023)
Esophageal stricture is a disorder that limiting patients’ capability to get adequate intake. Dysphagia and regurgitation are main problem that makes patient admit to the hospital. There are several causes that narrowing esophageal lumen; those could be intraluminal or extraluminal. Esophageal diverticulum is one of a kind. It is not easy to establish the diagnosis of diverticulum in esophagus segment since supporting examination needed were complex. Esophageal stricture treatment should be interdisciplinary approach because inappropriate management would increase risk of complication and lowering patient’s quality of life. The management of esophageal diverticulum could be challenging and its prognosis depends on the patient’s characteristic and comorbidity.